Man in India - Roy, Sarat Chandra, Rai Bahadur, 1871-1942 ([Calcutta, etc., A.K. Bose, etc.], 1921)
Print only
"A quarterly anthropological journal."
Founded and edited Mar. 1921-Mar. 1942 by S.C. Roy.
Keywords: Anthropology -- Periodicals; Ethnology -- India -- Periodicals; Anthropology -- India -- Periodicals; Antropologie; Anthropology; Ethnology; India